Evaluating the effectiveness of intravenous alteplase in patients with minor non-disabling stroke and severe large vessel stenosis: a retrospective study - Du, Qiong; Li, Xiaoxuan; Tang, Yangli; Li, Xuemei; Li, Xijun; Hou, Haichun; Yan, Yang; Liu, Xichang; Huang, Zhengbiao; Liu, Zhenxing; Xu, Hailong (Frontiers in Neurology, 2025)
AimThe efficacy of intravenous alteplase thrombolysis in patients with minor non-disabling acute ischemic stroke with severe large vessel stenosis or occlusion remains uncertain. This study aimed to assess the clinical effectiveness of intravenous alteplase therapy compared to dual antiplatelet therapy (DAPT) in this specific high-risk population.MethodsWe conducted a retrospective study of patients presenting with minor non-disabling strokes [National Institutes of Health Stroke Scale (NIHSS) score ≤ 5 with all item scores 0 or 1] and severe large vessel stenosis or occlusion across four hospitals in Yichang City, Hubei Province (January 2019–December 2024, n = 396). Propensity score matching (1:1 nearest-neighbor with caliper 0.2 SD) was performed to balance baseline characteristics. Multivariable logistic regression models with progressive adjustment for demographic, clinical, laboratory, and imaging variables were used to evaluate the association between the treatment allocation (intravenous alteplase vs. DAPT) and excellent functional outcomes [modified Rankin Scale (mRS) 0–1 at 90 days].ResultsAmong 396 included patients (median age 68 years, 67.9% male), 199 received alteplase treatment and 197 received DAPT. The alteplase group demonstrated significantly higher rates of excellent functional outcomes at 90 days compared to the DAPT group (79.9 vs. 56.9%, p < 0.001). with adjusted odds ratio of 3.17 (95% CI: 1.77–5.66) in the fully adjusted model. Conditional logistic regression analysis in the propensity score-matched cohort consistently showed superior efficacy of alteplase (OR: 3.24, 95% CI: 1.75–5.98). Safety outcomes did not differ significantly between groups with comparable rates of hemorrhagic transformation (3.0 vs 1.5%, p = 0.503), and symptomatic intracranial hemorrhage (1.5 vs. 0%, p = 0.248).ConclusionIn summary, for patients with minor non-disabling stroke and severe large vessel stenosis or occlusion, intravenous alteplase administered within 4.5 h is associated with significantly better functional outcomes compared to DAPT, without increasing the risk of hemorrhagic complications. These findings support the use of thrombolysis in this specific patient population and highlight the need for randomized controlled trials to confirm these results.